An overview of the biological functions and mechanisms of action of medicinal plants and seaweeds in the shrimp culture - Sajjad Pourmozaffar; Miriam Reverter; Saeid Tamadoni Jahromi; Ramasamy Harikrishnan; Mohammad Khalil Pazir; Noora Barzkar; Mansour Torfi Mozanzadeh; Behzad Sarvi; Marzieh Abolfathi; Ibrahim Adeshina; Siamak Behzadi; Abdullateef Raji (John Wiley & Sons Ltd, 2024)
Diseases are major constraints to developing large‐scale aquaculture practices in many countries. For decades, synthetic chemotherapeutic agents have been widely applied both as prophylactics and therapeutics to inhibit and control aquatic disease outbreaks. However, their use has become more restricted due to the negative impacts they have on the environment, the host and humans, as well as their limitations in preventing the emergence of antimicrobial‐resistant bacteria. Therefore, there is a growing interest in the use of medicinal plants and seaweeds as potential alternatives to antibiotics and other synthetic chemotherapeutics. Medicinal plants and seaweeds can enhance the immune systems of animals, thereby providing protection against numerous diseases while minimizing the adverse effects associated with synthetic chemotherapeutics. Furthermore, the advantages of medicinal plants and seaweeds, such as their effectiveness, easy availability and ability to be applied on a large scale, make them appealing for use in the aquaculture industry. The main goal of this study was to review the existing knowledge of the effects of medicinal plants and seaweeds, as well as their extracts, on shrimp growth, immune response and disease resistance against bacterial and viral agents. Moreover, this paper discusses the application of seaweeds in shrimp culture. We also conducted a literature review to identify gaps in the research and provide recommendations for further advancement in this field of study. Further studies should focus on evaluating other physiological aspects, such as feed and mineral utilization, enzyme activities and histological examination.